Getting older and living up to implicit followership theories: Implications for employee psychological health and job attitudes. Issue 2 (24th January 2020) - Stegmann, Sebastian; Braun, Stephan; Junker, Nina; van Dick, Rolf
Abstract: Age discrimination at work is a widespread destructive phenomenon that often takes subtle forms. Based on negative stereotypes about older employees, we argue that older employees often experience that they are perceived as less ideal followers than younger employees. We propose that older and younger employees do not differ in what they assume their supervisors expect of an ideal follower (implicit followership theories, IFTs). Thus, we hypothesize that older employees perceive that they compare less favorably to their supervisors' IFTs than younger employees (i.e., worse IFT‐fit). This should entail lower quality of the relationship between leader and follower (leader‐member‐exchange, LMX), which, in turn, should have detrimental effects on employees' health (i.e., burnout) and job attitudes (i.e., job satisfaction, turnover intentions, and identification). We tested our model in a field study with 379 employees. Results differed for ideal and counter‐ideal follower attributes. Concerning counter‐ideal follower attributes (e.g., being incompetent), age had the proposed negative effect on psychological health and job attitudes that mediated through IFT‐fit and LMX. Concerning ideal follower attributes (e.g., thinking ahead), older employees expected their supervisors not only to think less of them than of their younger colleagues, but also expected them to have less demanding IFTs—contrary to our expectations. Employee age was negatively related to psychological health and job attitudes, mediated through lower perceived IFTs, worse perceived appraisal of the actual employee and their joint effects on LMX.